THE EFFECT OF SOCIAL INFLUENCE AND HABIT ON USE BEHAVIOR OF GOJEK APPLICATION USERS IN THE MEDAN HELVETIA DISTRICT AREA - Rizkya Paulita Nasution; Beby Karina Fawzeea Sembiring; Syafrizal Helmi Situmorang (Universitas Efarina, 2023)
This research is intended to know the effect of social influence and habit on use behavior in the Medan Helvetia District. The population and sample in this study were 130 users of the Gojek application in Medan Helvetia District, and the sampling technique was accidental sampling. The data analysis technique used is multiple linear regression statistical analysis. The primary data used in this study consisted of social influence and habits on use behavior. The results of this research show that based on the partial test (t-test), social influence and habit have a significant effect on the variables of the use behavior. The simultaneous test (f-test), social influence and habit, significantly affect the variables of the use behavior.